A Paradigm Shift on the role of CIO’s in Cloud and IOT based Organizations - Jipson George Thoomkuzhy; Mohammed Nazeh (Society of Visual Informatics, 2018)
Cloud computing and IOT has transformed the way organizations across industries work. This review paper researched the role of the global CIO regarding their key employment capacities and their basic abilities and competencies which are required all together for a CIO to accomplish unrivaled hierarchical execution of the future business condition. The discoveries of this review will give insight to five key employment capacities and the basic competencies which we accept are fundamental to the role of the global CIO in the present and future business condition. The discoveries will additionally show that the global CIO role is winding up progressively and is key in driving development, hierarchical change and technological change. Consequently, the global CIO should be a visionary vital leader with eminent relational abilities and business keenness and the capacity to team up evenly over the central business capacities and with key business accomplices.About Six CIO interviews directed by the CIO Executive Council were investigated and reviewed as far as past journals which had recognized various key employment capacities and basic abilities and competencies for the role of a global CIO.The role of the Chief Information officer (CIO) has turned out to be progressively testing and mind-boggling as data correspondences innovation has turned out to be essential for most organizations. To date, there has been little research which has exactly inspected the roles and the basic competencies of the global CIO. An online overview of CIOs affirmed the significance of CIO competencies and highlighted the basic ones. An arrangement of the basic competencies of CIOs was analyzed in this review.The key discoveries demonstrate that the role of the global CIOs has progressed toward becoming progressively business engaged and vital in cloud and IOT based organizations. Eventually, how a CIO leads and deals with his/her ICT staff will enormously impact how effective a CIO is in the role. Be that as it may, the CIO still requires the knowledge of key innovation skills so, individual information or access to additional abilities is also essential in their role